Improved Model for GIC Calculation in the Mexican Power Grid - R. Caraballo; J. A. González‐Esparza; C. R. Pacheco; P. Corona‐Romero (Space Weather)
Abstract We present the first observations of geomagnetically induced currents (GIC) in the Mexican power grid and an improved model to calculate them. The new model comprises ca. 250 substations working at various voltage levels, a methodology to estimate geomagnetic disturbances (δB) at different points throughout the Mexican territory, and a 1D piecewise model that considers lateral variations in the ground conductivity. This is an improvement of a former uniform conductivity model presented previously to calculate our first GIC estimates (Caraballo et al., 2020). We compared the observed and calculated GIC between August and November 2021 at a coastal 400 kV substation. During this interval, five geomagnetic storms occurred (G1 and G2). The observed GIC exceeded 10 A during the most strong event; this shows a clear grid response even under weak geomagnetic perturbations that occurred during the solar minimum. Further comparison with the results of the former model suggests that the new 1D piecewise model yields better GIC estimates for the Mexican power grid.